Prostate Cancer: Biology, Incidence, Detection Methods, Treatment Methods, and Vaccines - Bartzatt, Ronald (Current Topics in Medicinal Chemistry, 2020)
Cancer of the prostate are cancers in which most incidences are slow-growing, and in the U.S., a record of 1.2 million new cases of prostate cancer occurred in 2018. The rates of this type of cancer have been increasing in developing nations. The risk factors for prostate cancer include age, family history, and obesity. It is believed that the rate of prostate cancer is correlated with the Western diet. Various advances in methods of radiotherapy have contributed to lowering morbidity. Therapy for hormone- refractory prostate cancer is making progress, for almost all men with metastases will proceed to hormone-refractory prostate cancer. Smoking cigarettes along with the presence of prostate cancer has been shown to cause a higher risk of mortality in prostate cancer. The serious outcome of incontinence and erectile dysfunction result from the cancer treatment of surgery and radiation, particularly for prostate- specific antigen detected cancers that will not cause morbidity or mortality. Families of patients, as well as patients, are profoundly affected following the diagnosis of prostate cancer. Poor communication between spouses during prostate cancer increases the risk for poor adjustment to prostate cancer. The use of serum prostate-specific antigen to screen for prostate cancer has led to a greater detection, in its early stage, of this cancer. Prostate cancer is the most common malignancy in American men, accounting for more than 29% of all diagnosed cancers and about 13% of all cancer deaths. A shortened course of hormonal therapy with docetaxel following radical prostatectomy (or radiation therapy) for high-risk prostate cancer has been shown to be both safe and feasible. Patients treated with docetaxel-estramustine had a prostate-specific antigen response decline of at least 50%. Cancer vaccines are an immune-based cancer treatment that may provide the promise of a non-toxic but efficacious therapeutic alternative for cancer patients. Further studies will elucidate improved methods of detection and treatment.
Keywords: Erectile dysfunction